Sistemas erp: uma contribuição ao estudo do ciclo de vida em uma instituição federal de ensino superior - Ferreira, David Luiz Silva (2014)
The use of ERP systems in brazilian public organizations represents a change in operating procedures quite significant and is the result of the worldwide movement "New Public Management" or "New Public Management", occurred from the 1980s, the government pricipalmente U.S. administrations , Great Britain and Sweden. The main feature of this movement is the adoption by government organizations of information and communication technologies (ICT) and operational technologies already tested as efficient from the private organizations. The ERP system arises in the early 1990s, released by the German company SAP, founded in 1972, with the R / 2 and R / 3 products, becoming a leader in this segment, becoming the product of information technology used by most large public and private organizations worldwide. The implementation of this type of information technology in organizations has as consequence the beginning of a state of organizational change, where all the people involved, planters, managers and operators get the reflexes arising from the adoption of new technology. In public organizations, especially in Brazilian IFES, there are few studies on the investigation of these reflections, which can be both difficult as benefits to be enjoyed by people. The aim of this study is to describe the implementation of an ERP system in a Brazilian IFES through the study of the life cycle of this system along with the difficulties and possible benefits of adopting this emerging information technology.